2018
DOI: 10.2196/resprot.8110
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Advanced Diagnostics and Treatment of Acute Stroke: Protocol for a Controlled Intervention Study

Abstract: ClinicalTrials.gov NCT03158259; https://clinicaltrials.gov/show/NCT03158259 (Archived by WebCite at http://www.webcitation.org/6wxNEUMUD).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…The primary outcome was to determine the difference in OTT between the intervention and control group. A power analysis (twosample, two-sided, power 0.80) determined a sample size of 86 thrombolyzed patients in each group to confirm a 30-minute difference in OTT [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome was to determine the difference in OTT between the intervention and control group. A power analysis (twosample, two-sided, power 0.80) determined a sample size of 86 thrombolyzed patients in each group to confirm a 30-minute difference in OTT [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Safety parameters were reported to an external safety committee of two experienced neurologists. The committee was blinded for study group and could stop the study if they found evidence for an unacceptable increase in SICH (>4%) or deaths [11]. Modified Rankin Scale (mRS) was analyzed as an ordinal scale (0-6) and dichotomized where mRS 0-2 was defined as favorable outcome (functionally independent).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that even the most reliable blood gas analyser at that time resulted in technic failure in approximately 20% of all applications [11]. Even when used by trained anaesthesiologists, procedural difficulties were encountered when attempting to draw an arterial blood sample in 10 out of 36 cardiac arrest patients undergoing resuscitation [9]. In a more heterogeneous population of critically ill patients, 34% of the arterial blood gas analyses could not be performed due to technical failure [12].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, blood glucose measurement has been possible in every ambulance in Denmark, and measurements of troponin or lactate can a be performed prehospitally [ 3 , 4 ]. The use of ultrasonography has increased diagnostic accuracy [ 5 7 ], and mobile prehospital CT scanners are currently being tested for use in patients with suspected cerebral thrombosis to facilitate immediate prehospital thrombolysis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%